Motives behind cooperation in finitely repeated prisoner's dilemma - Anujit Chakraborty (University of California, Department of Economics, 2022)
This paper deploys a novel experiment to compare four theories that explain both selfish and non-selfish cooperation. The four theories capture incomplete information (à la Kreps et al. (1982)) alongside the following four non-selfish motives: caring about others (Altruism), being conscientious about cooperation (Duty), enjoying social-efficiency (Efficiency-Seeking), and reciprocity (Sequential Reciprocity). Our experimental design varies the decline-rate of future rewards, under which these theories make contrasting predictions. We find that Efficiency-Seeking is the other-regarding behavior that fits the experimental data best. A Finite Mixture Model analysis finds that 40-49% of our subjects are selfish, 36-45% are Efficiency-seeking, 1-4% are Duty players, and 6-20% are Altruistic.
Keywords: C72; C73; C92; 330; Experimental Economics; Finitely Repeated Prisoner's Dilemma; Behavioral game theory